THU0003 CD4+ and B lymphocyte expression quantitative traits at rheumatoid arthritis risk loci in untreated early arthritis: implications for causal gene identification?. (15th June 2017) - Thalayasingam, N; Massey, J; Anderson, AE; Nair, N; Skelton, A; Lendrem, DW; Reynard, L; Cordell, HJ; Eyre, S; Barton, A; Isaacs, JD; Pratt, AG
Abstract : Background: Rheumatoid arthritis (RA) is a genetically complex disease of immune dysregulation. Genome-wide association scans (GWAS) have confirmed its association with variants at >100 genetic loci. Outside of the HLA region, accumulating data now highlight an overlap between these risk loci and cell-specific enhancer elements that is maximal in CD4+ lymphocytes, followed by B lymphocytes Objectives: Seeking insight into genetic risk mechanisms, we conducted and compared expression quantitative trait locus (eQTL) analyses of risk loci in CD4+ T cells and B cells from carefully phenotyped early arthritis patients naïve to therapeutic immunomodulation. Methods: 254 patients donated RNA and DNA from purified B and/or CD4+ T-cells within 4 hours of blood draw. Genotyping and global gene expression measurement were carried out using the Illumina Human CoreExome array and either HT12v4 or WG6v3 BeadChip arrays respectively. Variants in linkage disequilibrium (LD) with 101 confirmed non-HLA RA- SNPs (r 2 >0.8) were analysed, seeking evidence of cis - or trans - eQTLs according to whether associated probes were or were not within 4MB of these LD blocks. Results: Genes subject to cis eQTL effects common to both CD4+ and B-lymphocytes at RA risk loci were FADS1, FADS2, BLK, FCRL3, ORMDL 3 and GSDMB . At the 8p23 BLK-FAM167A locus, we found adjacent genes subject to eQTLs whose activity differed markedly between cell types, the FAM167A effect displaying striking B-lymphocyte specificity. By contrast, cis eQTLs acting on METTL21B, IKZF3, and PADI4 were unique to CD4+ lymphocytes, the latter two of these being identified for the first time in this cell subset. No trans eQTLs approached experiment-wide significance, and linear modelling did not identify a significant influence of biological co-variates (diagnosis, systemic inflammation, age) upon eQTL effect sizes. Conclusions: Our findings refine understanding of candidate causal genes in RA pathogenesis, providing an important platform from which downstream functional studies may be prioritised and directed towards particular cell types. References: Okada Y, Wu D, Trynka G, Raj T, Terao C, Ikari K, et al. Genetics of rheumatoid arthritis contributes to biology and drug discovery. Nature. 2014 Feb 20; 506(7488):376–381. Acknowledgements: Wellcome Trust, Academy of Medical Sciences, JGW Patterson Foundation, National Institute of Health Research, Pfizer. Newcastle researchers received infrastructural support via the Arthritis Research UK Centre of Excellence for the RA pathogenesis (RACE). JM and NN are funded by an MRC/Arthritis Research UK stratified medicine award (MR/K015346/1). Disclosure of Interest: N. Thalayasingam: None declared, J. Massey: None declared, A. Anderson: None declared, N. Nair: None declared, A. Skelton: None declared, D. Lendrem: None declared, L. Reynard: None declared, H. Cordell: None declared, S. Eyre: None declared, A. Barton: None declared, J. Isaacs: None declared, A. Pratt Grant/research support from: Pfizer